A Catalyst‐Free and Chemoselective Synthesis of Episulfides from Epoxides in 2, 3‐Butanediol without Formation of Poly(episulfide)s. Issue 16 (1st June 2017) - Aoyagi, Naoto; Endo, Takeshi
Abstract: Synthesis of episulfides from epoxides was studied under ambient conditions without catalysts. Detailed investigation showed that the conversion of epoxides and the selectivity of transformation to episulfides were highly affected by the choice of solvents. Phenyl glycidyl ether (PGE) is one of the most reactive of the commercially available epoxides, but it was not reacted with thiourea in bulk, tetrahydrofuran and acetonitrile. Primary alcohols and primary/secondary diol such as methanol, ethanol, 1, 4‐butanediol and 1, 2‐butanediol promoted the reaction of PGE with thiourea in high conversion; however, yield of corresponding episulfide was lower or moderate to accompanying with undesirable polymerizations such as poly(episulfide)s. In contrast, the use of 2, 3‐butanediol resulted in remarkably increased selectivity and yield of episulfide. The choice of sulfur sources had also effect on the selectivity and the reactivity. Potassium thiocyanate (KSCN) was more effective than the use of other sulfur sources. The combination of KSCN and 2, 3‐butanediol was the best reaction system for the synthesis of episulfides without formation of poly(episulfide)s. Abstract : Episulfides were obtained from various epoxides with potassium thiocyanate in polar protic solvents under ambient conditions without catalyst. Especially the use of 2, 3‐butandiol as a solvent, episulfides were afforded in high yield without polymerization of episulfide.